MIXED CONVECTION AND ENTROPY GENERATION OF A NANOFLUID FILLED CAVITY WITH A CORNER PARTITION AND FLEXIBLEWALL - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Begell House Inc, 2018)
In this study, the effects of a conductive corner partition and flexible sidewall in a CuO-water nanofluid-filled lid-driven square enclosure on mixed convective heat transfer were numerically examined using the finite element method. The top wall of the square cavity is moving with constant speed and the bottom wall of the cavity is heated. The side wall is made flexible. The effects of the Richardson number (between 0.01 and 20), elastic modulus of the flexible wall (between 103 and 105), size of the corner partition (between 0 and 0.6), and solid particle volume fraction (between 0 and 0.05) on the fluid flow, heat transfer characteristics and entropy generation rate were numerically investigated. It was observed that local and average heat transfer enhances for higher values of the Richardson number, elastic modulus of the flexible wall and solid particle volume fraction of the nanoparticles. An average heat transfer enhancement of 38.34% was obtained when the elastic modulus of the flexible wall was reduced from 105 to 103, and 32.10% of the average Nusselt number enhancement was obtained for 5% nanoparticle addition to the base fluid. The presence of the conductive corner partition deteriorated the local and average heat transfer, and average heat transfer reduction for 23.78% of was observed for a partition size of 0.6. Entropy generation rates for the fluid domain and solid domain of the conductive partition were found to be affected by the variation of those parameters.
Keywords: corner partition; flexible wall; nanofluid; finite element method